Faktor-Faktor yang Mempengaruhi Struktur Modal pada Perusahaan Industri Barang Konsumsi - Rika Rizky Ayuningtyas; Suhendro Suhendro; Purnama Siddi (Universitas Batanghari Jambi, 2020)
This study aims to determine the factors that influence capital structure. The independent variables in this study are asset structure, company size, liquidity and profitability. The population of this research is 43 consumer goods industry companies listed on the Indonesia Stock Exchange for the period of 2016-2018. By using purposive sampling technique, as many as 62 companies met the sample criteria. The method used is multiple linear regression. The results of this study indicate that simultaneously asset structure, company size, liquidity, and profitability variables affect the capital structure. The research results partially liquidity variables affect the capital structure. Meanwhile, the variable asset structure, company size, and profitability does not affect the capital structure.